The very small angle neutron scattering instrument at the National Institute of Standards and Technology. Issue 2 (27th February 2022) - Barker, John; Moyer, James; Kline, Steven; Jensen, Grethe; Cook, Jeremy; Gagnon, Cedric; Kelley, Elizabeth; Chabot, Jean Philippe; Maliszewskyj, Nicholas; Parikh, Chirag; Chen, Wangchun; Murphy, R. P.; et al.
Abstract : A description and the performance of the very small angle neutron scattering diffractometer at the National Institute of Standards and Technology are presented. Abstract : A description and the performance of the very small angle neutron scattering diffractometer at the National Institute of Standards and Technology are presented. The measurement range of the instrument extends over three decades of momentum transfer q from 2 × 10 −4 to 0.7 Å −1 . The entire scattering angle range from 8 × 10 −5 to π/6 rad (30°) can be measured simultaneously using three separate detector carriages on rails holding nine 2D detector arrays. Versatile choices of collimation options and neutron wavelength selection allow the q resolution and beam intensity to be optimized for the needs of the experiment. High q resolution is achieved using multiple converging‐beam collimation with circular pinholes combined with refractive lenses and prisms. Relaxed vertical resolution with much higher beam intensity can be achieved with narrow slit collimation and a broad wavelength range chosen by truncating the moderator source distribution below 4 Å with a Be crystalline filter and above 8 Å with a supermirror deflector. Polarized beam measurements with full polarization analysis are also provided by a high‐performance supermirror polarizer and spin flipper, capable of producing flipping ratios of over 100, along with a high‐efficiency 3 He polarization analyzer.